2011
DOI: 10.3109/13697137.2010.532251
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hysterectomy and/or oophorectomy on sexual satisfaction

Abstract: Patients were dissatisfied with frequency and communication, and they had high levels of avoidance before operation. In the postoperative period, sexual dissatisfaction increased. Although depression and anxiety decreased after the operation, we found that hysterectomy and/or oophorectomy had negative effects on sexual satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 40 publications
1
21
0
1
Order By: Relevance
“…40 Data are conflicting regarding the impact of hysterectomy on sexuality, with some studies suggesting hysterectomy improves sexual function 41Y43 and others reporting a worsening of sexual function. 44,45 However, the applicability of these studies to RRSO is limited because of the variability in their indications for hysterectomy, surgical approaches, severity of preoperative symptoms, and concurrent bilateral oophorectomy. One crosssectional study of 119 women following RRSO found no association between hysterectomy and sexual function, although 89% of the participants had undergone hysterectomy, and the study may not have been sufficiently powered to detect a difference.…”
Section: Menopause Status At Operationmentioning
confidence: 99%
“…40 Data are conflicting regarding the impact of hysterectomy on sexuality, with some studies suggesting hysterectomy improves sexual function 41Y43 and others reporting a worsening of sexual function. 44,45 However, the applicability of these studies to RRSO is limited because of the variability in their indications for hysterectomy, surgical approaches, severity of preoperative symptoms, and concurrent bilateral oophorectomy. One crosssectional study of 119 women following RRSO found no association between hysterectomy and sexual function, although 89% of the participants had undergone hysterectomy, and the study may not have been sufficiently powered to detect a difference.…”
Section: Menopause Status At Operationmentioning
confidence: 99%
“…Also, there may be consequences already reported in hysterectomized patients, including effects on gender identity and sexuality [27], decrease in sexual satisfaction and increase in sexual dysfunction [28,29].…”
Section: List Of Abbreviationsmentioning
confidence: 99%
“…Indeed, men who receive vasectomies are usually sure of their decision at the time, but are often grateful for the fact that vasectomies tend to be reversible should they decide to have children later on [29]. Finally, there is data suggesting that posthysterectomy, women experience a decrease in sexual satisfaction [30] and an increase in sexual dysfunction [31]. To ensure that prospective donors make informed, autonomous decisions, there is an added impetus to give a potential uterus donor both comprehensive information relating to giving up a healthy uterus and time to consider such a significant and irrevocable decision.…”
Section: Ethics In the Context Of Standard Practicementioning
confidence: 99%